Pengaruh Profitabilitas, Solvabilitas, dan Efisiensi Terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Mahardhika, Jakaria; Wahju Widajatun, Vincentia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of profitability (ROA), solvency (DER), and efficiency (TATO) on firm value (PBV) with firm size as a moderating variable among companies in the Basic Materials Sector, Basic Chemical Sub-Industry listed on the Indonesia Stock Exchange during the 2019–2023 period. The research employs a descriptive quantitative method using panel data from 14 companies, resulting in a total of 70 observations obtained from annual financial reports. The data were analyzed using multiple regression with the Moderated Regression Analysis (MRA) approach through EViews 12 software. The findings reveal that, partially, profitability and efficiency have a significant effect on firm value, while solvency has no significant effect. Furthermore, firm size strengthens the relationship between profitability and efficiency on firm value, yet fails to moderate the relationship between solvency and firm value. These results imply that higher profitability and efficient asset utilization can enhance firm value, particularly in larger firms, while the level of leverage does not significantly influence investor valuation. The study contributes to financial management literature by emphasizing the moderating role of firm size in the relationship between financial performance indicators and firm value in the Indonesian basic chemical industry.